Mengidentifikasi Keterbacaan Wacana Buku Teks Bahasa Indonesia Kelas IX Menggunakan Grafik Fry dan Raygor - Sri Syahputri; Tasya Amelia Saragi; Erika Cyntia Pebryanti Silitonga; Inayah Hanum; Safinatul Hasanah Harahap (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
This study attempted to examine the readability of Indonesian textbooks for grade IX of the 2013 Revised edition. This research uses descriptive qualitative method with observation technique. That is by direct observation on the discourse data that will be used as research material. The source of data in this study is in the form of written sources, namely in class IX textbooks. The data collected will be analyzed in accordance with the symptoms assessed in the study and then described. Each of the three parts of the discourse is sampled in the amount of 100 words from the total. Furthermore, it is determined the number of sentences in each sample described To estimate a readability there are many formulas that can be used, for example the Fry and Raygor graph formulas. Both look similar because they require similar data but there are still differences between them. Based on the results of the above research, it can be seen that the readability of textbooks, especially Indonesian textbooks for grade IX of the 2013 Revised edition, is at the readability level of 7-8. This indicates that at this approximate level, students can understand the textbook reading. This means that literacy problems continue to take root. So that improving literacy in the younger generation continues to be a special concern in finding the right improvement method. Keyboard: Raygor, textbook, Frygor, readability, discourse